Providing Culturally Relevant Services for International Black African Collegians in the United States: A Guide for Student Affairs Professionals - Onyenekwu, Ifeyinwa Uchechi (Journal of International Students, 2017)
The experience of international Black African collegians (IBAC) in U.S. higher education has not been adequately investigated, particularly as it relates to understanding the diversity within Black and international student populations. In this manuscript, I offer seven culturally relevant suggestions for student affairs professionals, all of which build on my professional experiences working with IBAC in student affairs as well as my research with Nigerian collegians in U.S. higher education.